Knowledge attitude among marriage women of reproductive age towards vesico vaginal fistula in Kebbi State Nigeria - Saudat Abdullahi Basheer (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2012